An exploration of user engagement and communication strategies on Spotify: a uses and gratifications perspective - Mohamed, Elsir Ali Saad; Al Aawad, Haitham Abdelrahman; Abasher, Mathani Hassan; Al-Rached, Saleh Obaid; Altaher, Abdulla Ebrahim (Frontiers in Communication, 2025)
This study investigated the communication gap between Spotify and its users, focusing on messaging consistency, user-specific experiences, and feedback mechanisms. By analyzing data from students at Umm Al Quwain University, the study revealed a potential disconnect between how Spotify communicates and how users expect to be addressed. This disconnect could negatively impact user engagement and satisfaction. Key findings highlighted the need for personalized communication tailored to user needs, improved channels for user feedback, and the active integration of this feedback into Spotify’s communication strategies. Bridging this communication gap, Spotify can enhance user experience, solidify its user-centric approach, and potentially strengthen its position as a leader in the digital music landscape.